2013
DOI: 10.1177/1078155213508440
|View full text |Cite
|
Sign up to set email alerts
|

First-line trastuzumab plus taxane-based chemotherapy for metastatic breast cancer: Cost-minimization analysis

Abstract: Our economic analysis shows that although the costs of the two trastuzumab plus taxane regimens are similar, they may contribute to the on-going debate about the availability and use of innovative chemotherapy drugs, in particular in human epidermal growth factor receptor 2-positive metastatic breast cancer with new therapies such as trastuzumab-DM1 and pertuzumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Indeed, considering triple-negative breast cancer in France, bevacizumab costs EUR 13,330,631 per year, hence the decision of most other countries to reverse the approval of bevacizumab in breast cancer, as there was no improvement in OS in addition to significant costs. Besides, the drug is considered not to be cost-effective, based on its cost per year of life extended [14]. The RIBBON-2 trial which involved 684 women with HER2-negative metastatic breast cancer who had already received one course of chemotherapy has demonstrated that adding bevacizumab to chemotherapy as a second-line treatment increased PFS by around 2 months; in this study, some patients taking bevacizumab also experienced longer time to disease progression, as 2 months remains an average [15].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, considering triple-negative breast cancer in France, bevacizumab costs EUR 13,330,631 per year, hence the decision of most other countries to reverse the approval of bevacizumab in breast cancer, as there was no improvement in OS in addition to significant costs. Besides, the drug is considered not to be cost-effective, based on its cost per year of life extended [14]. The RIBBON-2 trial which involved 684 women with HER2-negative metastatic breast cancer who had already received one course of chemotherapy has demonstrated that adding bevacizumab to chemotherapy as a second-line treatment increased PFS by around 2 months; in this study, some patients taking bevacizumab also experienced longer time to disease progression, as 2 months remains an average [15].…”
Section: Resultsmentioning
confidence: 99%
“…Taxanes can be used as single agent or in combination with other treatments such as the combination of anthracycline with taxanes that improve the quality of life better than anthracycline or taxanes treatment alone [ 5 , 133 ]. In addition, combination of taxanes plus biological drugs such as trastuzumab showed improvement in overall survival in patients with MBC [ 134 ]. Furthermore, combination of lapatinib with docetaxel and trastuzumab can be used as a first-line treatment of HER2-positive MBC [ 135 ].…”
Section: Treatments Of Metastatic Breast Cancermentioning
confidence: 99%
“…It is a sound deduction that a treatment aimed at reducing the blood supply of a tumor would also reduce the delivery of any other therapy, such as chemotherapy, which is also important for radiotherapy for anti-angiogenesis agents and may reduce the oxygen supply necessary for a response to radiotherapy ( 16 ). However, synergism of anti-angiogenetics and chemotherapeutics has been observed in patients with colon cancers ( 105 ), non-small cell lung cancers ( 106 ), and breast cancers ( 107 , 108 ). One explanation is that with the blockage of VEGF signaling, anti-angiogenetics induces a normalization of newly formed vessels, and thus, reduces the interstitial tissue pressure (ITP) within tumors, allowing enhanced delivery of chemotherapy to the tumors ( 7 ).…”
Section: Strategy For Advanced Osteosarcoma In the Era Of Targeted Thmentioning
confidence: 99%